Biodiversity of Rhizoctonia solani in Phaseolus vulgaris Seeds in East Delta of Egypt - Khalid M. Ghoneem; Deiaa A. El-Wakil; Mohamed I. M. Ahmed; Hisham M. Kamel; Ehsan M. Rashad; Abdulaziz A. Al-Askar; Elsherbiny A. Elsherbiny; Amira A. Ibrahim (Agronomy, 2023)
Seventy-eight common bean (Phaseolus vulgaris L.) seed samples were collected from twenty-one field locations across six governorates (Ismailia, Sharkia, Port Said, South Sinai, North Sinai, and Suez) in the East Delta region of Egypt between 2021 and 2022. Thirty-five Rhizoctonia solani Kühn were isolated. Sharkia had the highest percentage of R. solani isolates (RS) from the collected samples (59%), followed by Ismailia, South Sinai, Suez, North Sinai, and Port Said (49.7%, 36.7%, 33%, 29.2%, and 27.8%, respectively). Pathogenicity tests proved that the seven highest-virulence strains of R. solani had a pre-emergence damping off ranging from 17% to 30% and a post-emergence damping off ranging from 11% to 20%. The seven most pathogenic isolates were identified using the Internal Transcribed Spacer (ITS) with code numbers as follows: R. solani RSA1, R. solani RIT2, R. solani RIF3, R. solani RSoR4, R. solani RNB5, R. solani RSzA6, and R. solani RPS11. Principle component analysis (PCA), which depends on the pathogenicity result and soil variables, revealed that soil texture and soil water holding capacity (MWHC) were the most effective factors in grouping and clustering the studied R. solani isolates from the different locations into two groups. From this study, it can be established that the biodiversity of R. solani in the East Delta area of Egypt depends on changes in the environmental conditions and soil variables. The soil type and pH variables have the greatest impact on R. solani diversity, followed by the humidity-holding ability and soil porosity.